Faddeev-Yakubovsky technique for weakly bound systems - Hadizadeh, M. R. [UNESP]; Yamashita, M. T. [UNESP]; Tomio, Lauro [UNESP]; Delfino, A.; Frederico, T. (My University, 2011)
The Faddeev-Yakubovsky formalism for the study of three- and four-boson bound states have been derived in a partial wave representation for separable potentials and by considering only the s-wave channel contribution. In order to be able to study the weakly three- and four-boson bound states the obtained formalism is simplified for a zero range interaction and the integral equations are regularized by a subtraction technique.